Os novos rumos do trabalho - emprego e desemprego: uma análise das práticas discursivas de jovens das camadas populares e sua percepção sobre os novos paradigmas do mundo do trabalho - Parenti, Ana Flávia da Costa (2009)
The present work consists in a qualitative study on low class young people and their real opportunities of being admitted to a job in the labor market. It´s been used the technique of discourse analysis applying on young students from 15 to 24 years old, living in a poor part of the São Paulo city, and studying in a free government school. It´s aimed to focus on what they think about their success of getting a job, if they believe they can do it, by means of analysing their speechs. In the course of the explanation, it´s presented the economic and politic circumstances Brazil has been through last decades and their impacts over what constitutes the object of this study. A pannel of Brazil economic and social index also is presented. Focus group technique has been used to check the opinions of the participants about their perspectives, how they plan to overthrough the predictable difficults coming along, how they interact and what they think. Discours analysis was the method used. Besides, the study is conducted according to the constructionism philosophy, which considers the linguistic-conceptual aspects of the phenomenon. Linking ideas were set down on a map to clarify the main emerging themes and the importance they seem to have for the interviewed people